RECOMMENDATIONS ON DIAGNOSIS AND TREATMENT OF URINARY TRACT INFECTIONS IN CHILDREN - T. V. Margiyeva; O. V. Komarova; T. V. Vashurina; I. S. Kostyushina; O. A. Zrobok; T. V. Sergeyeva; A. N. Tsygin (Union of pediatricians of Russia, 2016)
Given very high prevalence of urinary tract infection (UTI) in the setting of renal pathology in children, timely disease identification, adequate antibacterial treatment and, if necessary, anti relapse therapy are of extreme importance. It is known that recurrent UTI is a risk factor of renal damage progression and development of renal failure. The given clinical recommendations on UTI diagnosis and management are based on the evidence-based approach. This helps to optimize work of pediatricians and pediatric nephrologists.